Training needs assessment of health care professionals in a developing country: the example of Saint Lucia. Issue 1 (December 2016) - Gaspard, Janice; Yang, Che-Ming
Abstract Background Continuing education (CE) is crucial for quality improvement in health care. The needs assessment of CE helps ensure effectiveness. However, such an assessment necessitates certain techniques that are unfamiliar to health care communities in developing countries. This study identifies the needs of providing CE to health care personnel in Saint Lucia. Methods This study was designed as a questionnaire survey to investigate the demographics, training needs, and preferred approaches to improve performance of the target population. The study population included the health care professionals of major public health care facilities in Saint Lucia. We used the World Health Organization–adopted Hennessy Hicks Training Needs Analysis Questionnaire, a self-reported close-ended structured questionnaire with a core set of 30 items. These items refer to tasks that are central to the role of health care professionals and are categorized into six superordinate categories: research/audit, communication/teamwork, clinical skills, administrative, managerial/supervisory, and continuing professional education. Results In total, 208 questionnaires were distributed; the response rate was 66.8 %, and most respondents were nurses. The need for continuing professional education was rated the highest priority, followed by research/audit activities. The evidence suggests that most respondents required training in communication skills, management, clinical skills, and research methods. Conclusions Providing training according to the needs is vital, particularly in developing countries. The present research methodology and findings offer perspectives on how to conduct needs assessment and offer reference points for developing countries whose background and health care environment are similar to those of Saint Lucia.